Increasing the Existence of Urban Tourism Through the Development Strategy of Marine Tourism Destinations in Kendari City - Farid Said; Jujuk Ferdianto; Agus Agus (CV. Publikasi Indonesia, 2023)
The purpose of this study is to determine the Increasing the Existence of Urban Tourism. The research method used is a qualitative method with a descriptive approach. Qualitative research is a method based on the philosophy of postpositivism used to examine the natural condition of objects where researchers are key instruments in data collection techniques. The result obtained is the geographical characteristics of the city of Kendari with the urban area surrounding the bay illustrates the uniqueness of the urban area owned, therefore the Kendari City Government should make this bay as a branding in introducing itself to attract the attention and interest of tourists to visit Kendari City. The conclusion that can be is that the development of tourism facilities and infrastructure has not been optimal, especially the arrangement of the Kendari Bay area as marine tourism that is not in accordance with the tourism architecture because it does not have good management management, so that it can have an impact on damage to natural ecosystems and socio-cultural gaps in the community.